The Role of Asia Raya Newspaper as a Japanese Propaganda Instrument, 1942 – 1945 - Jihan Fahira; Abdi Mubarak Syam (Warisan: Journal of History and Cultural Heritage, 2026)
The Japanese occupation of Indonesia from 1942 to 1945 transformed colonial society through the implementation of a wartime economic system designed to sustain Japanese military expansion in the Pacific. Within this context, mass media functioned not merely as channels of information but as strategic instruments of economic propaganda and colonial discourse. This study examines how the newspaper Asia Raya, published in Jakarta, was utilised to build public support for the Japanese war agenda and to disseminate ideological narratives on economic mobilisation, social discipline, and cultural integration. The research employs a historical method with a qualitative approach through textual analysis of Asia Raya archival materials from Khastara, complemented by books and scholarly journal sources. The findings reveal that Asia Raya systematically framed economic policies, labour mobilisation, and wartime sacrifice as collective moral responsibilities, thereby legitimising Japanese political authority in occupied Indonesia. The study demonstrates that the newspaper operated not only as a propaganda medium but also as a mechanism for shaping colonial perceptions and regulating public consciousness during wartime. This research contributes to the historiography of the Japanese occupation by emphasising the interconnection among wartime media, economic propaganda, and colonial power relations.